Предмет: Алгебра,
автор: Аноним
Обчислити:
Ответы
Автор ответа:
0
для удобности написания я заменю корень из 5 на х -> x^2=5
((3+x)/(3-x))-3x/2 =
((3+x)*2 - 3x*(3-x)) / 2*(3-x) =
(6+2x-9x +3x^2) / 2*(3-x) =(6-7x+3*5) / 2*(3-x) =
(-7x+21) / 2*(3-x) =7(3-x) / 2*(3-x) = 7/2
((3+x)/(3-x))-3x/2 =
((3+x)*2 - 3x*(3-x)) / 2*(3-x) =
(6+2x-9x +3x^2) / 2*(3-x) =(6-7x+3*5) / 2*(3-x) =
(-7x+21) / 2*(3-x) =7(3-x) / 2*(3-x) = 7/2
Похожие вопросы
Предмет: Биология,
автор: Аноним
Предмет: Математика,
автор: nursiternazarova46
Предмет: Русский язык,
автор: ivan2007sam
Предмет: Химия,
автор: Sara4433